Islamic Leadership, Emotional Intelligence, and Spiritual Intelligence on Passion of Work and Performance - Panyiwi Kessi, Andi Makkulawu; Suwardi, Wisda Zulaeha; Mukhtar, Afiah; Asmawiyah, A.; Pratiwi AR, Dhita (Manunggal Halim Jaya, 2022)
This study aims to test and analyze empirically the influence of Islamic leadership, emotional intelligence, and spiritual intelligence on morale, and the influence of Islamic leadership, emotional intelligence, spiritual intelligence, and passion of work on employee performance, as well as the effect of Islamic leadership, emotional intelligence, Spiritual intelligence on employee performance. Employee performance through and employee morale. The research was carried out in all work units at the 140 Islamic Private lecturers in the scope of LLDIKTI-IX. Data from the questionnaire were analyzed using the Structural Equation Model by AMOS. The study results found that Islamic leadership positively and significantly affected morale, emotional intelligence, and spiritual intelligence, increasing employee morale. Employee performance improves with high Islamic leadership and increased confidence. Emotional intelligence and spiritual intelligence have a positive but not significant effect on employee performance. The position of morale in the research model is not to be a mediating variable (intervening) in explaining the influence of Islamic leadership on employee performance. The role of morale in the research model is a perfect mediation variable (complete mediation) in explaining the effect of emotional intelligence and spiritual intelligence on employee performance. To improve employee performance, emotional intelligence cannot do it directly.